2022
DOI: 10.1097/md.0000000000029347
|View full text |Cite
|
Sign up to set email alerts
|

CONSORT-Characteristics and metabolic phenotype of gut microbiota in NAFLD patients

Abstract: Patients with nonalcoholic fatty liver disease (NAFLD) have symptoms of a gut microbiota disorder with abnormal amino acid and glycolipid metabolism. This study was designed to analyze the characteristics of gut microbiota in patients with NAFLD, predict the gut microbiota phenotype, explore its role in the diagnosis of NAFLD, and establish its significance in disease progression. The characteristics of the gut microbiota in NAFLD patients (n = 28, 45.8 ± 14.2 years, male/female = 18/10) and healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…Ge and co-workers have studied fecal metabolomics in patients with NAFLD and healthy controls using UHPLC/MS/MS [53]. All participants were overweight and/or had visceral obesity.…”
Section: Fecal Metabolomics and Metagenomics Identifying The Gut Micr...mentioning
confidence: 99%
See 2 more Smart Citations
“…Ge and co-workers have studied fecal metabolomics in patients with NAFLD and healthy controls using UHPLC/MS/MS [53]. All participants were overweight and/or had visceral obesity.…”
Section: Fecal Metabolomics and Metagenomics Identifying The Gut Micr...mentioning
confidence: 99%
“…Interestingly, nicotinamide adenine dinucleotide (NAD + ) is being studied in clinical trials as a potential target to treat NAFLD [54]. However, Ge et al failed to show differences in the fecal levels of nicotinate between the healthy and NAFLD groups [53]. Altered pyrimidine metabolism was reflected in lower fecal levels of uracil in the NAFLD patients.…”
Section: Fecal Metabolomics and Metagenomics Identifying The Gut Micr...mentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 38 studies [11][12][13][14][15][16][17][18][19][20][21]33,35,36,[38][39][40][41][44][45][46]48,49,[51][52][53]56,[58][59][60][61][62][64][65][66][68][69][70][71]74,75,78,79,82,84 provided data for α-diversity (Table 1), which was then assessed using eight indices, namely richness/evenness (Shannon T A B L E 2 Total analysis, stratified analysis, and sensitivity analysis among alpha diversity.…”
Section: α-Diversitymentioning
confidence: 99%
“…Many studies have shown an association between gut dysbiosis and metabolic syndrome, obesity, type 2 diabetes, and NAFLD [ 16 , 17 , 18 , 19 ]. Ge et al showed that adult patients with NAFLD demonstrated lower diversity and a Firmicutes/Bacteroides (F/B) ratio than the controls [ 20 ]. Chierico et al found an increased abundance of Bradyrhizobium, Anaerococcus, Peptoniphilus, Propionibacterium acnes, Dorea , and Ruminococcus , and a decreased abundance of Rikenellaceae and Oscillospira in the gut microbiome of children with NAFLD [ 16 ].…”
Section: Introductionmentioning
confidence: 99%